Mortgaging the ancestors : ideologies of attachment in Africa. - Shipton, Parker MacDonald (Yale agrarian studies series., 2009)
"This interdisciplinary book is about land, belonging, and the mortgage - and how people of different cultural backgrounds understand them in Africa. Drawing on years of ethnographic observation, Parker Shipton discusses how people in Africa's interior feel about their attachment to family, to clan land, and to ancestral graves on the land. He goes on to explain why systems of property, finance, and mortgaging imposed by outsiders threaten Africa's rural people." "The book looks briefly at European and North American theories on private property and the mortgage, then shows how these theories have played out as attempted economic reforms in Africa. They affect not just personal ownership and possession, he suggests, but also the complex relationships that add up to civil order and episodic disorder over a longer history. Focusing particular attention on the Luo people of Kenya, Shipton challenges assumptions about rural economic development and calls for a broader understanding of local realities in Africa and beyond." -- Présentation de l'éditeur.